2021
DOI: 10.1038/s41419-020-03286-z
|View full text |Cite
|
Sign up to set email alerts
|

Role of Sciellin in gallbladder cancer proliferation and formation of neutrophil extracellular traps

Abstract: Apart from primary tumor development and metastasis, cancer-associated thrombosis is the second cause of cancer death in solid tumor malignancy. However, the mechanistic insight into the development of gallbladder cancer (GBC) and cancer-associated thrombosis remains unclear. This study aimed to investigate the mechanistic role of Sciellin (SCEL) in GBC cell proliferation and the development of venous thromboembolism. The expression level of SCEL was determined by immunohistochemical staining. Roles of SCEL in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 48 publications
1
13
0
Order By: Relevance
“…Normally induced by pro-inflammatory factors during infection, NETs can also be stimulated by cancer cells and cancer-associated fibroblasts (CAF) in the absence of infection [ 40 ] , which hijacks antimicrobial immune system for cancer cell proliferation and metastasis (Table 2 ). The crosstalk between tumor cells and neutrophils can be mediated by tumor-derived chemokines, including granulocyte colony-stimulating factor (G-CSF) [ 41 , 42 ], IL-8 [ 43 , 44 ] and CXC Chemokine Receptor (CXC) ligands [ 45 ], which have been implicated in protumour NETosis in multiple murine models. In addition to chemokines, tumoral Cathepsin C, a cysteine protease essential for catalytic activation of serine proteases, has been shown to induce neutrophil ROS production and IL-1β secretion, thus promoting neutrophil infiltration and NETs formation [ 46 ] .…”
Section: Nets Formation In the Context Of Cancermentioning
confidence: 99%
“…Normally induced by pro-inflammatory factors during infection, NETs can also be stimulated by cancer cells and cancer-associated fibroblasts (CAF) in the absence of infection [ 40 ] , which hijacks antimicrobial immune system for cancer cell proliferation and metastasis (Table 2 ). The crosstalk between tumor cells and neutrophils can be mediated by tumor-derived chemokines, including granulocyte colony-stimulating factor (G-CSF) [ 41 , 42 ], IL-8 [ 43 , 44 ] and CXC Chemokine Receptor (CXC) ligands [ 45 ], which have been implicated in protumour NETosis in multiple murine models. In addition to chemokines, tumoral Cathepsin C, a cysteine protease essential for catalytic activation of serine proteases, has been shown to induce neutrophil ROS production and IL-1β secretion, thus promoting neutrophil infiltration and NETs formation [ 46 ] .…”
Section: Nets Formation In the Context Of Cancermentioning
confidence: 99%
“…A study discovered that CTSC secreted by tumors promotes the formation of NETs in breast cancer cells. CTSC induces neutrophil ROS production and the formation of NETs by activating the neutrophil membrane-bound PR3-interleukin-1β (IL-1β)-p38 axis [ 83 ].…”
Section: Molecular Pathway Of Netosis Stimulated By Various Agonistsmentioning
confidence: 99%
“…A recent study done by Li et al examined the function of Sciellin (SCEL), a precursor to the cornified envelope, which is a protective barrier in the upper epidermis [ 129 ], in gallbladder cancer progression. Using a co-culture experiment, the authors found that SCEL induced expression of NETs and citrullinated-histone 3, which is a critical marker of NET formation [ 130 ]. Similar to gallbladder cancer, SCEL is markedly elevated in pancreatic cancer [ 131 ].…”
Section: Immune Characterization Of the Tme And Impact On The Ecmmentioning
confidence: 99%